Impact of compression ratio and injection parameters on the performance and emissions of a DI diesel engine fueled with biodiesel-blended diesel fuel - SAYIN, CENK; GÜMÜŞ, METİN (PERGAMON-ELSEVIER SCIENCE LTD, 2011)
This work investigates the influence of compression ratio (CR) and injection parameters such injection timing (IT) and injection pressure (IP) on the performance and emissions of a DI diesel engine using biodiesel (%5, 20%, 50%, and 100%) blended-diesel fuel. Tests were carried out using three different CRs (17, 18, and 19/1), ITs (15 degrees, 20 degrees, and 25 degrees CA BTDC) and IPs (18, 20 and 22 MPa) at 20 N m engine load and 2200 rpm. The results showed that brake specific fuel consumption (BSFC), brake specific energy consumption (BSEC), and nitrogen oxides (NOx) emissions increased while brake thermal efficiency (BTE), smoke opacity (OP), carbon monoxide (CO) and hydrocarbon (HC) decreased with the increase in the amount of biodiesel in the fuel mixture. The best results for BSFC, BSEC and BTE were observed at increased the CR, IP, and original IT. For the all tested fuels, an increase in IP, IT and CR leaded to decrease in the OP. CO and MC emissions while NO emissions increase. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Biodiesel; Diesel engine; Compression ratio; Injection timing; Injection pressure; OIL METHYL-ESTER; EXHAUST EMISSIONS; COMBUSTION; PRESSURE